Seismic reliability functions for multistorey frame and wall-frame systems. - Alamilla, Jorge L.
Seismic reliability functions of multistorey frame systems are expressed as values of Cornell's βindex in terms of two alternative measures of the earthquake intensity, normalized with respect to the yield displacement or to the deformation capacity of a simplified model of the global behaviour of the system obtained by pushover analysis. The safety margin is defined as the difference of the natural logarithms of the intensity that leads to collapse and that assumed to act on the system. The problem of defining a deformation capacity for a multistorey system is circumvented in this manner. The method proposed is illustrated through its application to several reinforced concrete rigid frames, including both column-and-beam and wall-frame systems. Ground motion excitations are representative of those recorded at soft soil sites in the Valley of Mexico. A comparison is made of the reliability functions obtained on the basis of the gross section or the cracked section of reinforced concrete members. The results show that the reliability functions do not only depend on the expected values of the normalized intensity, but also on its dispersion, which is sensitive to the ratio of the fundamental period of the system to the dominant period of the ground motion. Some comments are presented about the establishment of reliability-based seismic design criteria for generic systems.
Keywords: Reliability functions; Ground motion; Unbounded lateral response